استدعاء الموروث التاريخي في القصة القصيرة مجموعات زكريا تامر القصصية أنموذجا - مجدي حسين شحادات (Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2018)
الملخص: يعد التراث الإنساني مصدرا غنيا للأدباء؛ بفضل ما يقدمه لهم من مواد تراثية وقصص تاريخية، وسير شعبية، وشخصيات بطولية؛ ولذا فإن عددا منهم  يستدعي في أدبه التراث بمواده المختلفة في محاولة منهم لإحياء الماضي من أجل فهم الواقع، ولا عجب أن نجد الأديب زكريا تامر يستدعي التراث الإنساني في مجموعاته القصصية بشكل واضح كالشخصيات التاريخية والأدبية والدينية والشعبية؛ ومن هنا فقد جاءت هذه الدراسة لتكشف عن مفهوم الموروث التاريخي في مجموعات الأديب زكريا تامر القصصية، وآليات توظيفه ودلالاته، كما حددت الدراسة  أنواع الشخصيات التاريخية ونماذجها، متبعة المنهجين: الاستقصائي للشخصيات التاريخية في مجموعاته القصصية، والمنهج التحليلي لأهم هذه الشخصيات. الكلمات الأساسية: زكريا تامر، الموروث التاريخي، دلالات التوظيف، الشخصيات التاريخية، نماذج تاريخية.Summary : The heritage of mankind is a rich source for writers because it provides them with heritage materials, historical stories, folklore and heroic figures. Therefore, a number of writers invoke various materials of heritage in their writings in an attempt to revive the past in order to understand the reality of the present. It is no wonder that the writer Zakaria Tamer invokes the heritage of mankind in his collections of stories clearly, such as historical, literary, religious and popular figures. Hence, this study is intended to reveal the historical heritage concept in the writer, Zakaria Tamer’s collection of stories, the employed mechanisms and their indications. The study also defines the types of historical figures and their models, by applying two approaches, that is the analytical approach for historical figures in his collections of stories and the analytical approach for the most important characters. Zakaria Tamer, historical heritage, indications of employment, historical figures, historical models.